THE USE OF COMPETENCY-BASED MODULES IN FACILITATE PROSPECTIVE TEACHER VOCATIONAL FOR DESIGN SYLLABUS AND LESSON PLAN - suherman, amay; komaro, mumu; berman, ega taqwali (Journal of Mechanical Engineering Education, 2020)
This study aims to obtain information from prospective vocational teacher students about the benefits of competency-based modules in facilitating them to design syllabus and lesson plan (RPP). This study used a qualitative method with research participants who were students of mechanical engineering education as vocational teacher candidates at a state university in Bandung. The informants involved in this study were five students consisting of three men and two women who had already carried out a lesson planning course. The method used to collect data is Focus Group Discussion (FGD) which is used to obtain general information and individual interviews to obtain more specific data. The results showed that the availability of competency-based modules was very helpful for students in guiding the preparation of syllabus and lesson plans. So that, this research will have implications for the achievement of student competencies in planning the teaching and learning process according to the demands of the 2013 curriculum.